2018
DOI: 10.1093/pasj/psy100
|View full text |Cite
|
Sign up to set email alerts
|

Is the infrared background excess explained by the isotropic zodiacal light from the outer solar system?

Abstract: This paper investigates whether an isotropic zodiacal light from the outer Solar system can account for the detected background excess in near-infrared. Assuming that interplanetary dust particles are distributed in a thin spherical shell at the outer Solar system (> 200 AU), thermal emission from such cold (< 30 K) dust in the shell has a peak at far-infrared (∼ 100 µm). By comparing the calculated thermal emission from the dust shell with the observed background emissions at far-infrared, permissible dust am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(71 reference statements)
1
1
0
Order By: Relevance
“…Our F150W and F200W NIRCam diffuse light limits in Figure 13 are in line with the 1.1-1.6 μm CIBER detections of Matsuura et al (2017) and Sano et al (2020; purple triangles in Figure 13), and with the SKYSURF upper limits in the HST/ WFC3 F140W and F160M filters of Carleton et al (2022). These papers, as well as Tsumura (2018) and Korngut et al (2022), suggested that some very dim spherical-or nearly spherical-Zodiacal component could be missing from the Kelsall et al (1998) model. Kelsall et al (1998) also noted that a dim spherical Zodiacal component could have been missed in their model of the COBE/DIRBE data.…”
Section: Jwst Sky-sb Estimates and Possible Limits To Diffuse Lightsupporting
confidence: 83%
See 1 more Smart Citation
“…Our F150W and F200W NIRCam diffuse light limits in Figure 13 are in line with the 1.1-1.6 μm CIBER detections of Matsuura et al (2017) and Sano et al (2020; purple triangles in Figure 13), and with the SKYSURF upper limits in the HST/ WFC3 F140W and F160M filters of Carleton et al (2022). These papers, as well as Tsumura (2018) and Korngut et al (2022), suggested that some very dim spherical-or nearly spherical-Zodiacal component could be missing from the Kelsall et al (1998) model. Kelsall et al (1998) also noted that a dim spherical Zodiacal component could have been missed in their model of the COBE/DIRBE data.…”
Section: Jwst Sky-sb Estimates and Possible Limits To Diffuse Lightsupporting
confidence: 83%
“…Software: Astropy: http://www.astropy.org (Astropy Collaboration et al 2013, 2018; IDL Astronomy Library: https://idlastro.gsfc.nasa.gov (Landsman 1993); Photutils: https://photutils.readthedocs.io/en/stable/ (Bradley et al 2020); ProFound: https://github.com/asgr/ProFound (Robotham et al 2017(Robotham et al , 2018; ProFit: https://github.com/ICRAR/ProFit (Robotham et al 2018); SourceExtractor: SourceExtractor: https://www.astromatic.net/software/sextractor/ or https:// sextractor.readthedocs.io/en/latest/ (Bertin & Arnouts 1996).…”
mentioning
confidence: 99%